Corporate Integrity Culture and Compliance: A Study of the Pharmaceutical Industry* - Altamuro, Jennifer L. M.; Gray, John V.; Zhang, Haiwen (Helen) (Contemporary Accounting Research, 2022)
ABSTRACT This study examines corporate integrity culture—that is, a firm's shared values and behaviors related to compliance, trustworthiness, and ethics. Different from prior research that associates culture measures with general firm‐level outcomes, we evaluate the pervasiveness of the integrity culture within an organization across two disparate business functions: operations and financial reporting. We first develop a measure of corporate integrity culture based on firms' internal control environments and show that, as predicted, weak integrity culture contributes to both operational and financial non‐compliance. We next document the predicted positive contemporaneous association between operational and financial non‐compliance, controlling for the integrity culture reflected in the internal control environment. Given the organizational and physical distances and lack of day‐to‐day interactions between the two business functions, we infer that management's “tone at the top” likely affects non‐compliance in both functions. Finally, for firms with existing operational non‐compliance, we find more negative market reactions to accounting restatements and higher CEO turnover propensities following restatements. These results indicate that top management must consistently reinforce a culture of compliance and integrity, lest it decay throughout the organization. Our results also imply that regulators evaluating compliance in specific functions could benefit from reviewing compliance in other functions within the firm.